How much biomass do plant communities pack per unit volume? - Proulx, Raphaël; Rheault, Guillaume; Bonin, Laurianne; Roca, Irene Torrecilla; Martin, Charles A.; Desrochers, Louis; Seiferling, Ian (PeerJ, 2015)
Aboveground production in terrestrial plant communities is commonly expressed in amount of carbon, or biomass, per unit surface. Alternatively, expressing production per unit volume allows the comparison of communities by their fundamental capacities in packing carbon. In this work we reanalyzed published data from more than 900 plant communities across nine ecosystems to show that standing dry biomass per unit volume (biomass packing) consistently averages around 1 kg/m3 and rarely exceeds 5 kg/m3 across ecosystem types. Furthermore, we examined how empirical relationships between aboveground production and plant species richness are modified when standing biomass is expressed per unit volume rather than surface. We propose that biomass packing emphasizes species coexistence mechanisms and may be an indicator of resource use efficiency in plant communities.
Keywords: Packing density; Biodiversity; Plant geometry; Ecosystem; Self-thinning; Species coexistence